Intercultural Communication in Translation - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (Barca Academy Publishing, 2020)
Abstract. The article deals with revealing issues and prospects of intercultural communication, as well as the way translation functions in the latter overcoming the difficulties emerging in the “translation of cultures”. The author comes to the conclusion that the choice of a suitable way of translation depends on the function of the text being translated and the aim of translation, though other, more subjective factors may render influence as well, e.g. the translator‘s personal aesthetic preferences.
Keywords: intercultural communication; translation; source text; target text; source language; target language